Distribution of MT1 melatonin receptor immunoreactivity in the human hypothalamus and pituitary gland: Colocalization of MT1 with vasopressin, oxytocin, and corticotropin-releasing hormone - Wu, Ying-Hui; Zhou, Jiang-Ning; Balesar, Rawien; Unmehopa, Unga; Bao, Aimin; Jockers, Ralf; Van Heerikhuize, Joop; Swaab, Dick F. (Journal of comparative neurology (1911), 2006)
Melatonin is implicated in numerous physiological processes, including circadian rhythms, stress, and reproduction, many of which are mediated by the hypothalamus and pituitary. The physiological actions of melatonin are mainly mediated by melatonin receptors. We here describe the distribution of the melatonin receptor MT1 in the human hypothalamus and pituitary by immunocytochemistry. MT1 immunoreactivity showed a widespread pattern in the hypothalamus. In addition to the area of the suprachiasmatic nucleus (SCN), a number of novel sites, including the paraventricular nucleus (PVN), periventricular nucleus, supraoptic nucleus (SON), sexually dimorphic nucleus, the diagonal band of Broca, the nucleus basalis of Meynert, infundibular nucleus, ventromedial and dorsomedial nucleus, tuberomamillary nucleus, mamillary body, and paraventricular thalamic nucleus were observed to have neuronal MT1 receptor expression. No staining was observed in the nucleus tuberalis lateralis and bed nucleus of the stria terminalis. The MT1 receptor was colocalized with some vasopressin (AVP) neurons in the SCN, colocalized with some parvocellular and magnocellular AVP and oxytocine (OXT) neurons in the PVN and SON, and colocalized with some parvocellular corticotropin‐releasing hormone (CRH) neurons in the PVN. In the pituitary, strong MT1 expression was observed in the pars tuberalis, while a weak staining was found in the posterior and anterior pituitary. These findings provide a neurobiological basis for the participation of melatonin in the regulation of various hypothalamic and pituitary functions. The colocalization of MT1 and CRH suggests that melatonin might directly modulate the hypothalamus–pituitary–adrenal axis in the PVN, which may have implications for stress conditions such as depression. J. Comp. Neurol. 499:897–910, 2006. © 2006 Wiley‐Liss, Inc.